Azhari, Ainul LINGKUNGAN PENDIDIKAN DAN PENGARUHNYA DALAM MOTIVASI BELAJAR PESERTA DIDIK DALAM HADIS NABI SAW - Dul Jalil, Ainul Azhari (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Students who have high motivation for learning show great attention to learning activities and have satisfactory results and vice versa. In addition, the awards given to students are very effective in motivating them to carry out learning activities. In this case we can also understand that it is related to the educational environment which can have an influence in motivating students' learning from the perspective of the Hadith of the Prophet SAW. This research is qualitative research, using analytical descriptive methods. And this research is also library research, using content analysis as a technique for analyzing the data, because this research relies on text and aims to provide a description of the research results. This research explains that Rasulullah Saw explained the importance of building a good educational environment so that it can increase good learning motivation within a student, whether in the family environment, school/madrasah environment or social-community environment. The family environment (parents) plays a very significant role in the process of children's religious education. In the hadith, the Prophet SAW also explains that through a family environment that provides faith in children, they can have learning motivation that touches aspects of students' extrinsic motivation. The school environment has a very big influence on students' learning motivation, based on the hadith above, learning motivation in the school environment is influenced by a teacher who has depth of knowledge, masters the subject matter, teaching methods, and also understands the basics of education, because this is as a means to arouse and motivate students in their learning process. And the community environment plays an important role in students' learning motivation through their peers. Through a hadith, the Prophet SAW explains that students' closeness to peers can influence students' development, including students' enthusiasm or motivation to learn.